STRUKTUR KETATANEGARAAN ISLAM DALAM PEMIKIRAN IMAM AL-MAWARDI - Fastafat Nayke br. Simanjuntak; Andra Ramadhan Nasution; Ray Habbib Bayhaqqi; Muhammad Raihan Tanjung; Abd Hafiz Hadrami Maha (Jurnal Ilmu Hukum dan Keadilan, 2026)
Leadership in Islam is a fundamental pillar in preserving religious existence and maintaining worldly order. This research aims to dissect the political thoughts of Imam al-Mawardi regarding the structure of the Islamic state, which includes the institution of imamah (head of state), the council of ahl al-hall wa al-aqd (electorate body), and the wizarah system (ministry). The research method employed is library research with a descriptive-analytical approach, referring to primary sources such as Al-Ahkam as-Sulthaniyah and Qawanin al-Wizarah wa Siyasat al-Mulk. The results indicate that al-Mawardi conceptualizes leadership as a mandate that must be collectively upheld (fardhu kifayah) to ensure justice. The legitimacy of leadership is strengthened through the role of ahl al-hall wa al-aqd as a representation of the people's sovereignty in succession and power oversight mechanisms. Furthermore, al-Mawardi systematizes the distribution of administrative authority through wizarah al-tafwidh (ministry with full mandate) and wizarah al-tanfidh (executive-technical ministry) to achieve governmental efficiency. This study concludes that the integration of these three institutions demonstrates the flexibility of al-Mawardi's thought, which maintains strong relevance to modern governmental administrative restructuring today.